Renal biopsy correlation between indications and histopathology diagnosis - Ashaq Parrey; Imtiyaz Ahmad; Khurshid Banday; Shabir Rather (Archives of Clinical Nephrology - Peertechz Publications, 2018)
Introduction: Renal biopsy is a procedure in which a sample of renal tissue is obtained for microscopic examination. Renal biopsy has contributed greatly to the classification of intrinsic renal diseases and, therefore, to a better knowledge of the pathogenesis involved. Although there are many studies regarding Renal Biopsy. There is little literature regarding correlation between indications and histopathology Diagnosis especially from India. Patients and Methods: Patients who presented with clinical and/or laboratory features of renal disease, whose diagnosis were uncertain with non invasive modalities and fulfilled the requirement for renal biopsy were subjected to renal biopsy Aims and objectives: The aim of this study was to find out the correlation between indications and histopathology of renal biopsy.  Results: In this prospective study 115 renal biopsies were performed in 70 males and 45 females. The mean age of males were 36 ± 14.3 and in females mean age was 29.6 + 12.8. The most common age group biopsied was between 19-45yrs of age both among males (58.6%) and females (66.7) respectively. The number of patients below 18yrs of age was 21, 11 male and 10 female. Patients above the age of 45 were 23. 18 male and 5 females. The most common indication for renal biopsy was protinuria with hematuria and subnephrotic protinuria 26 patients each followed by nephrotic syndrome 25 patients. IgA nephropathy was the most common histopathology diagnosis (15.7%). The second most common histopathology diagnosis was Minimal change disease (10.4%) patients, however all these patients had nephrotic syndrome and normal renal biopsy on histology as no electron microscopy was done. Nephrosclerosis was third most common histopathology diagnosis seen (8.7%) patients. Focal segmental glomerulosclerosis was reported in (7.8%), Membranous glomerulonephritis in (7%), Lupus nephritis in (7%) Mesangiocapilary glomerulonehritis in (7%), chronic graft rejection in 3 (2.6%) all these three patients had presented with post, transplant azotemia. Acute tubular necrosis was reported in 5 (4.2%) patients, chronic interstitial nephritis in (5.2%) patients. In 6 patients (5.2%) biopsy were inconclusive which showed either blood clot, medullary tissue.  Conclusion: Renal biopsy is one of the most important diagnostic modality with nephrologists. In our study most common indication for renal biopsy was Protinuria and Hematuria and most common histopathology diagnosis was IgA nephropathy.